Mechanics of moving contacts involving functionally graded multiferroics (Archives of Mechanics - Test, 2023)
This article introduces solution procedures for moving contacts involving functionally graded multiferroic coatings. A moving rigid punch of a flat or a triangular profile is assumed to be in contact with a multi-layer medium comprising magneto-electro-elastic coating layers, elastic interlayers, and an elastic substrate, that is modelled as a half-plane. The formulation is based on wave equations of plane elastodynamics and Maxwell’s equations. Applying Fourier and Galilean transformations, a singular integral equation of the second kind is derived for each of the flat and triangular punch problems. An expansion-collocation technique utilizing Jacobi polynomials is developed to numerically solve the integral equations. Proposed procedures are verified through comparisons to the results available in the literature. Parametric analyses carried out considering functionally graded magneto-electro-elastic coatings demonstrate the effects of the property variation profile, punch speed, and coating thickness on contact stresses, electric displacement, and magnetic induction. The methods presented could be of use in analysis and design studies of multiferroic layered systems subjected to moving contacts.